The Impact of Cosmetic Advertisements on Instagram on the Trends of Jordanian Women - Abdallah, Nisreen Riad; Nayel, Marah Mohammad (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to identify the elements and factors that influence Jordanian women’s attention to cosmetic medical Instagram ads. And identifying elements that attract Jordanian women’s attention to cosmetic medical Instagram ads. Methods: This study is considered a descriptive research that relied on the media audience survey approach. The study was conducted on a sample of (250) individuals from the study population, which is Jordanian women. Those aged from 20 to 51 years and over in the cities of Amman and Irbid. To achieve the objectives of the study, the study relied on the questionnaire as a tool for collecting data. Results: The study reached several results, the most important of which are: (53.8%) of the female respondents performed cosmetic medical procedures after being exposed to cosmetic medical advertisements on Instagram. The study showed that the most prominent elements that aroused Jordanian women’s interest in viewing cosmetic medical advertisements on Instagram were the display of the results of the cosmetic medical procedure. On people (before and after), it came in first place, being the most important elements. One of the most prominent factors that attract Jordanian women’s attention to seeing cosmetic medical ads on Instagram is the popularity of the advertised product (the brand), with an arithmetic average of (3.28). Among the most prominent patterns of exposure was the appearance of cosmetic medical advertisements (2 to 5) times more frequently among Jordanian women (49.2%). Conclusion: Focus on the content of the advertisement on social media sites, the validity of the information provided in it, and the extent of its clarity and accuracy, by presenting the nature of the medical procedure to gain the consumer’s trust and convince him of the procedure and the extent of his need for it in reality.